Palaeolandscapes in archaeology : lessons for the past and future - Carson, Mike T. (London: Routledge, 2022)
"What can we learn about the ancient landscapes of our world, and how can those lessons improve our future in the landscapes that we all inhabit? Those questions are addressed in this book, through a practical framework of concepts and methods, combined with detailed case studies around the world. The chapters explore the range of physical and social attributes that have shaped and re-shaped our landscapes through time. International authors contributed the latest results of investigating ancient landscapes (or "palaeolandscapes") in diverse settings of tropical forests, deserts, river deltas, remote islands, coastal zones, and continental interiors. The case studies embrace a liberal approach of combining archaeological evidence with other avenues of research in earth sciences, biology, and social relations. Individually and in concert, the chapters offer new perspectives on what the world's palaeolandscapes looked like, how people lived in these places, and how communities have engaged with long-term change in their natural and cultural environments though successive centuries and millennia. The lessons are paramount for building responsible strategies and policies today and into the future, noting that many of these issues from the past have gained more urgency today. This book reaches across archaeology, ecology, geography, and broader studies of human-environment relations that will appeal to general readers. Specialists and students in these fields will find extra value in the primary datasets and in the new ideas and perspectives. Furthermore, this book provides unique examples from the past, toward understanding the workings of sustainable landscape systems"--
What can we learn from palaeolandscapes in archaeology? / Mike T. Carson -- Potenial contributions of palaeolandscape archaeology : building strength through diversity / Mike T. Carson -- 25 years of geoarchaeological research on Palaeoindian landscapes : a look back at the discipline / Andrea K.L. Freeman -- Pathways along the Pacific : using early stone tools to reconstruct coastal migration between Japan and the Americas / Ian Buvit, Karisa Terry and Masami Izuho -- From wetlands to deserts : the role of water in the prehistoric occupatin of eastern Jordan / Lisa A. Maher, A.J. White, Jordan Brown, Felicia De Peña and Christopher J.H. Ames -- Creating living predictive models of coastal palaeoenvironmental landscapes : Georgia, USA / Lindsey E. Cochran, Victor D. Thompson and Bryan Tucker -- The domestic landscape and household resilience Actuncan, Belize /Kara Fulton and David W. Mixter -- Holocene sea-level change and evolution of prehistoric settlements around the Yangtze Delta Region / Yijie Zhuang and Shenglun Du -- Palaeolandscapes, radiocarbon chronologies, and the human settlement of southern lowland and island Papua New Guinea / Ben Shaw -- Kisim save long graun : understanding the nature of landscape change in modelling Lapita in Papua New Guinea / Glenn R. Summerhayes -- How island peoples adapt to climate change : insights from studies of Fiji's hillforts / Patrick D. Nunn, Elia Nakoro, Roselyn Kumar, Meli Nanuku and Mereoni Camailakeba -- 3500 years in a changing landscape : the House of Taga in the Mariana Islands, Western Micronesia / Mike T. Carson and Hsiao-chun Hung -- What have palaeolandscapes revealed about the past and for the future? / Mike T. Carson.
Includes bibliographical references and index.
Keywords: Landscape archaeology -- Case studies; Landscape assessment -- Case studies; Paleolithic period; Prehistoric peoples -- Casestudies; Human ecology -- Case studies